NCLB-A Threat or a Challenge to Public Education? A Reply to Edmondson and Shannon - Micahel J. Opuda (Journal of Research in Rural Education, 2003)
The authors are correct with their opening statement. However, it is the authors who are setting up the readers by suggesting that Shelley's experience with the Pennsylvania Reading First Initiative is proof that the "Bush Administration's" No Child Left Behind Act (NCLB, 2002) is a vast right wing conspiracy to privatize the public school and to usurp the authority of local schools and school boards.